UPAYA INTERNATIONAL OLYMPIC COMMITTEE (IOC) DALAM MENINGKATKAN KESETARAAN GENDER DI OLIMPIADE TAHUN 2017-2020 - Rachel Patricia (2022)
The focus of this research is to describe the many efforts of the International Olympic Committee (IOC) which have made progress in promoting gender equality in the realm of sport through the Olympic events and in particular for the female athletes. These efforts were born in various forms of action plans, annual agendas and other formal rules that have suppressed the emergence of women's discrimination issues in the implementation of the 2017-2020 Olympics. The research methodology is descriptive qualitative with data collection techniques through library research and internet-based research. This technique uses primary data collection in the form of official theoretical documents and secondary sources of related information and becomes a comparison according to the subject matter in the form of data, journals. This study uses the main concept, namely Gender Equality formulated by the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) and the Non-State Actor (NSA) theory as a sharpening knife in discussing how the role of the IOC as an International Organization in improving gender equality in international realm.